ANALYSIS OF JOB STRESS AFFECTING PERFORMANCE OF TECHNICAL TEACHERS - Rizvi, M A; Mangal, Anu (PEOPLE: International Journal of Social Sciences, 2018)
In this modern society job stress is a much talked complex phenomena leading to many disastrous consequences. Moderate level of stress that motivates a teacher is good. But as per the review of literature at international and national levels scenarios; some of the findings of the study reveals that majority of teachers faces serious problems of job stress due to various reasons such as work overload, lack of resources, role ambiguity, fair/less compensation, inadequate work environment etc. Also poor relations with colleagues, students’ indiscipline, lack of support from higher authorities, negative community attitude, farrago of thoughts related to profession and improper trainings contributes greatly in enhancing the problem. The quality of Technical education is serious concern of current situation which poses many issues to the future of technical youth. In this research it is tried to analyses the causes of stress and impact on quality because of stress. This will be done by designing the questionnaire depicting various reasons of stress in the educational Institutions as mentioned above. After that analysis will be done before coming the conclusion by applying various statistical methods on the data collected. The results will help us in identifying the key factors impacting quality of Technical Teachers. Hence this research is expected to contribute towards increase in the productivity of teachers in technical education. In future this research can be applied to the teacher community as a whole.